Biomarker identification from next-generation sequencing data for pathogen bacteria characterization and surveillance. (November 2015) - Zhao, Weizhong; Chen, James J; Foley, Steven; Wang, Yuping; Zhao, Shaohua; Basinger, John; Zou, Wen
Aim: The purpose was to develop an analytical pipeline for specific gene analysis and biomarker discovery from next generation sequencing (NGS) data.Materials & methods: As a test case, the fliC gene reference sequences of 24 Salmonella enterica strains of 13 serotypes and NGS reads of 32 serovar Newport, 48 Montevideo and 115 Enteritidis outbreak isolates were retrieved from the National Center for Biotechnology Information database.Results: Establishment of an analytical pipeline consisting of four steps: reference sequences retrieval and template sequence determination; NGS sequence reads retrieval; multiple sequence alignments and phylogenetic analysis; data mining and biomarker discovery.Conclusion: The pipeline developed provides an effective bioinformatics tool for genetic diversity clarification and marker sequences discovery for pathogen characterization and surveillance.